Assessing Malaysian crowdsourcing platforms using web of system performance (WOSP) model - Habbal, Adib M. Monzer; Chit, Suwannit Chareen; Ahmad, Rahayu; Mahmod, Musyrifah (2015)
Crowdsourcing allows organizations and individuals to tap into a large pool of people to accomplish tasks. Recent growth in crowdsourcing has triggered Malaysia to venture into crowdsourcing initiatives. This study intends to assess the performance of crowdsourcing platforms in Malaysia using the Web of System Performance (WOSP) model.The results give insights on the current state of crowdsourcing platforms in Malaysia and highlight the gaps that exist in these platforms. This eventually help to enhance the design of current platforms and promote higher uptake of crowdsourcing among Malaysians.